2003
DOI: 10.4269/ajtmh.2003.68.294
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Schistosoma Mansoni in Human Cerebrospinal Fluid

Abstract: Cerebrospinal fluid (CSF) and serum samples from patients suspected of having neuroschistosomiasis (NS) were evaluated by an enzyme-linked immunosorbent assay. Monoclonal antibodies of various immunoglobulin isotypes (IgM, IgA, IgE, total IgG, IgG1, IgG2, IgG3, and IgG4) were used to detect antibodies against Schistosoma mansoni soluble egg antigen (SEA) and soluble worm adult preparation (SWAP). Of the 83 CSF samples tested, 55% were reactive to SEA (26% were reactive only to SEA and 29% to both SEA and SWAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…1,2 Schistosomiasis is an infection caused by digenetic trematode platyhelminths of the genus Schistosoma, and the three main species are S. mansoni, S. japonicum, and S. hematobium. 3,4 The species S. mansoni infects approximately 12 million persons in Brazil, which characterizes this country as an endemic area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Schistosomiasis is an infection caused by digenetic trematode platyhelminths of the genus Schistosoma, and the three main species are S. mansoni, S. japonicum, and S. hematobium. 3,4 The species S. mansoni infects approximately 12 million persons in Brazil, which characterizes this country as an endemic area.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral lesions are caused primarily by S. japonicum, whereas spinal cord lesions are usually caused by S. mansoni and S. haematobium. 2 In patients in Brazil with fatal HSM, autopsies showed that 26% have brain involvement. 7 Reports of magnetic resonance imaging (MRI) findings associated with CNS schistosomiasis have described expansive lesions with variable enhancement patterns, such as diffuse, spotty, nodular, or central linear and nodular.…”
Section: Introductionmentioning
confidence: 99%
“…Serological testing is one of the frequently used diagnostic criteria for neuroschistosomiasis (Ferrari et al , 1995; Magalhães-Santos et al , 2003; Gryseels et al , 2006; Ferrari, 2010) but it is prone to cross-reactivity with other helminths, even with aetiologically relevant species such as Taenia solium (Pammenter et al , 1992). Egg-antigen immune complexes are usually detectable in the CSF of neuroschistosomiasis patients but are not routinely assessed in diagnostic testing (Ferrari et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is also supported by the analysis of CSF, which typically shows pleocytosis with increased lymphomonocytes, high CSF protein concentration and, in half of cases, eosinophilia 18. There are several recent studies on the role of CSF serology; antibodies are demonstrated in up to 60% of patients 19. Nevertheless, a definitive diagnosis can only be made by demonstrating eggs in the CNS on biopsy.…”
Section: Discussionmentioning
confidence: 99%